Strategi Pengelolaan Kualitas Air di UPTD BBIAT Waiheru Kota Ambon - Pirhel, Pirhel; Tuhumena, Lolita C.; Pattipeilohy, Christian E. (University of Pattimura, 2024)
The currently aquaculture have prospects that good is fish cultivation and influenced by thecnical factor and non-thecnical that determine as a requiement for cultivation business. The technical factor thar direct to influenced or failed towards cultivaation technical activity such as water quality. If there is a decrease in water quality can caused by inclusion of heavy metals to waters. The monitoring of water quality that carried out in UPTD BBIAT Waiheru only limited on physical parameters, while monitoring towards chemical parameters such as heavy metal content not done, so that not obtained an overall water quality information. For that researched needs to be done which aims to formulated direction of management water quality on UPTD BBIAT Waiheru. Ths researched by done on months November-December 2019, at UPTD BBIAT Waiheru. Water sampling used purposive sampling. Analysa method is SWOT and AHP. Based on the results of study incicated ther are six strategys direction of management water quality at UPTD BBIAT Waiheru and order of priority through analysis AHP is : 1) fulfillment of supporting facilities and infrastructures, 2) improvement of human resources capacity 3) improvement of society awareness related utilization of water resources,4) improvement of inventory, Identification and supervision towards water pollution source ,5) improvement of operational budget, and 6) improvement of CBIB certificate.